Mis-Educative Martial Law – The Fate of Free Discourse and the Moral Judgment Competence of Polish University Students from 1977 to 1983 - Nowak, Ewa; Lind, Georg (ETHICS IN PROGRESS, 2019)
The reprinted paper refers to Georg Lind and his colleagues’ MCT-based FORM study conducted at several European universities in 1977-1983, including Polish ones. After a short phase of democratization, in 1981 Polish society suddenly faced martial law. That experience had an impact on Polish students moral-, discursiveand democratic competences, as measured by MCT. When Ewa Nowak started her Alexander von Humboldt Foundation supported research stay under the supervision of Professor Georg Lind (University of Konstanz, 2008-2010), they were inspired to revisit and discuss the puzzling Polish research findings of 1981/3. According to their main hypothesis, martial law restricted free speech at universities, and free speech is a key facilitator of the development of moral and democratic competence. In 2018, after a decade of collaborative research on moral and democratic competence, Lind, Nowak and colleagues started a new international MCT study in several Central- and East European countries to examine the impact of the contemporary constitutional crisis in Poland (and the institutional crisis within the European Union) on students’ moral and democratic competencies. In 2018/9 the 40th anniversary of the Moral Competence Test (MCT) and Konstanz Method of Dilemma Discussion (KMDD) will be celebrated. We would like to provide you with the most recent research findings soon.